tìm x : x+3/17 +x+2/18=x+7/14 + x+5/5
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(12\left(x-3\right)=5\left(x-1\right)+4\)
\(\Rightarrow12x-36=5x-5+4\)
\(\Rightarrow12x-5x=-5+4+36\)
\(\Rightarrow7x=35\)
\(\Rightarrow x=5\)
\(-6\left(x-7\right)+2\left(x+10\right)=x-18\)
\(-6x+42+2x+20=x-18\)
\(-6x+2x-x=-18-20-42\)
\(-5x=-80\)
\(x=16\)
\(7\left(2x-1\right)-12\left(x-5\right)=3\)
\(\Rightarrow14x-7-12x+60=3\)
\(\Rightarrow14x-12x=3-60+7\)
\(\Rightarrow2x=-50\)
\(\Rightarrow x=-25\)
\(\left|2x-1\right|=17\)
\(\Leftrightarrow\orbr{\begin{cases}2x-1=17\\2x-1=-17\end{cases}}\)
\(\Leftrightarrow\orbr{\begin{cases}x=9\\x=-8\end{cases}}\)
\(\left|8-3x\right|=14\)
\(\Leftrightarrow\orbr{\begin{cases}8-3x=14\\8-3x=-14\end{cases}}\)
\(\Leftrightarrow\orbr{\begin{cases}x=-2\\x=\frac{22}{3}\end{cases}}\)
a: \(=\dfrac{17}{19}\cdot\dfrac{19}{17}\cdot\dfrac{4}{5}=\dfrac{4}{5}\)
b: \(=\dfrac{14}{7}\cdot\dfrac{7}{6}=2\cdot\dfrac{7}{6}=\dfrac{14}{6}=\dfrac{7}{3}\)
c: =13/14(4/5+1/5)=13/14
\(\dfrac{17}{19}\times\dfrac{12}{15}\times\dfrac{19}{17}.\\ =\dfrac{17}{19}\times\dfrac{19}{17}\times\dfrac{12}{15}.\\ =1\times\dfrac{12}{15}=\dfrac{12}{15}.\\ \left(\dfrac{5}{7}+\dfrac{9}{7}\right)\times\dfrac{21}{18}.\\ =2\times\dfrac{7}{6}=\dfrac{7}{3}.\\ \dfrac{4}{5}\times\dfrac{13}{14}+\dfrac{13}{14}\times\dfrac{1}{5}.\\ =\left(\dfrac{4}{5}+\dfrac{1}{5}\right)\times\dfrac{13}{14}.\\ =1\times\dfrac{13}{14}.\\ =\dfrac{13}{14}.\)
2,
a) \(315-\left(135-x\right)=215\)
\(\Rightarrow135-x=315-215\)
\(\Rightarrow135-x=100\)
\(\Rightarrow x=135-100\)
\(\Rightarrow x=35\)
b) \(x-320:32=25\cdot16\)
\(\Rightarrow x-10=5^2\cdot4^2\)
\(\Rightarrow x-10=20^2\)
\(\Rightarrow x-10=400\)
\(\Rightarrow x=410\)
c) \(3\cdot x-2018:2=23\)
\(=3\cdot x-1009=23\)
\(\Rightarrow3\cdot x=1032\)
\(\Rightarrow x=1032:3\)
\(\Rightarrow x=344\)
d) \(280-9\cdot x-x=80\)
\(\Rightarrow280-x\cdot\left(9+1\right)=80\)
\(\Rightarrow280-10\cdot x=80\)
\(\Rightarrow10\cdot x=280-80\)
\(\Rightarrow10\cdot x=200\)
\(\Rightarrow x=20\)
e) \(38\cdot x-12\cdot x-x\cdot16=40\)
\(\Rightarrow x\cdot\left(38-12-16\right)=40\)
\(\Rightarrow x\cdot10=40\)
\(\Rightarrow x=40:10\)
\(\Rightarrow x=4\)
a) 3x – 15 = 25 – 5x
=> 3x + 5x = 25 + 15
=> 8x = 40
=> x = 5
b) 3x - 17 = 2x – 7
=> 3x - 2x = -7 + 17
=> x = 10
c) 2x – 17 = – (3x – 18)
=> 2x - 17 = -3x + 18
=> 2x + 3x = 18 + 17
=> 5x = 35
=> x = 7
d) 3x – 14 = 2(x – 9) + 1
=> 3x - 14 = 2x - 18 + 1
=> 3x - 2x = -18 + 1 + 14
=> x = -3
f) (x – 5)2 = 9
\(\Rightarrow\left[{}\begin{matrix}x-5=3\\x-5=-3\end{matrix}\right.\)
\(\Rightarrow\left[{}\begin{matrix}x=8\\x=2\end{matrix}\right.\)
a) Ta có: \(3x-15=25-5x\)
\(\Leftrightarrow3x-15-25+5x=0\)
\(\Leftrightarrow8x-40=0\)
\(\Leftrightarrow8x=40\)
hay x=5
Vậy: x=5
b) Ta có: \(3x-17=2x-7\)
\(\Leftrightarrow3x-17-2x+7=0\)
\(\Leftrightarrow x-10=0\)
hay x=10
Vậy: x=10
c) Ta có: \(2x-17=-\left(3x-18\right)\)
\(\Leftrightarrow2x-17=-3x+18\)
\(\Leftrightarrow2x-17+3x-18=0\)
\(\Leftrightarrow5x-35=0\)
\(\Leftrightarrow5x=35\)
hay x=7
Vậy: x=7
d) Ta có: \(3x-14=2\left(x-9\right)+1\)
\(\Leftrightarrow3x-14=2x-18+1\)
\(\Leftrightarrow3x-14-2x+18-1=0\)
\(\Leftrightarrow x+3=0\)
\(\Leftrightarrow x=-3\)
Vậy: x=-3
f) Ta có: \(\left(x-5\right)^2=9\)
\(\Leftrightarrow\left[{}\begin{matrix}x-5=3\\x-5=-3\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x=8\\x=2\end{matrix}\right.\)
Vậy: \(x\in\left\{2;8\right\}\)